2022
DOI: 10.3390/antiox11112274
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Calorie Restriction Induces a Transcriptional Cytoprotective Response in Embryonic Liver Partially Dependent on Nrf2

Abstract: Background: Calorie restriction is known to enhance Nrf2 signaling and longevity in adult mice, partially by reducing reactive oxygen species, but calorie restriction during pregnancy leads to intrauterine growth retardation. The latter is associated with fetal reprogramming leading to increased incidence of obesity, metabolic syndrome and diabetes in adult life. Transcription factor Nrf2 is a central regulator of the antioxidant response and its crosstalk with metabolic pathways is emerging. We hypothesized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Furthermore, GSTA1 regulates the body's antioxidant capacity, and its expression level is positively correlated with oocyte quality (Habeos et al., 2022). Large follicular granulosa cells, with a notable developmental advantage, exhibit significantly higher GSTA1 expression compared to small follicular granulosa cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, GSTA1 regulates the body's antioxidant capacity, and its expression level is positively correlated with oocyte quality (Habeos et al., 2022). Large follicular granulosa cells, with a notable developmental advantage, exhibit significantly higher GSTA1 expression compared to small follicular granulosa cells.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, TCF4 has been demonstrated to play a crucial role in oocyte maturation, and it serves as a pivotal gene influencing litter size traits in goats (Shi et al, 2019;Sun et al, 2023). Furthermore, GSTA1 regulates the body's antioxidant capacity, and its expression level is positively correlated with oocyte quality (Habeos et al, 2022). Large follicular granulosa cells, with a notable developmental advantage, exhibit significantly higher GSTA1 expression compared to small follicular granulosa cells.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…George I. Habeos et al demonstrated that calories restricted by the mother increased the expression of genes involved in the integrative reaction to stress as well as the fetal liver's antioxidant and cytoprotective enzymes. These changes are particularly significant as they may be how adult mice respond to various stimuli, including toxins, excessive nutrient intake, and food shortage (41). The identified alterations in metabolic and antioxidant/cytoprotective genes offer insights into the potential mechanisms that the impact of maternal calorie restriction throughout the long term on the offspring's response to environmental challenges, nutrient imbalances, and limited food availability.…”
Section: In Vivo Modelmentioning
confidence: 99%
“…Contrary to hypothetical cellular effect of Piezo1 activation, antioxidation induced by Piezo1 activation has also been discovered in hepatocytes. Nrf2 is an important antioxidant and anti-inflammatory regulator promoting the expression of glutathione-S-transferases (Gst) and NAD(P)H: quinone oxidoreductase 1 (Nqo1) [ 105 , 106 ]. Piezo1 activation in hepatocyte increases the level of Nrf2 and Nqo1/Gsta1 genes to reduce cell death and mitochondrial oxidative stress [ 67 ].…”
Section: The Main Cellular Effects Of Piezo1 In Digestive Systemmentioning
confidence: 99%